The impact of school resources on women's earnings and educational attainment : findings from the national longitudinal survey of young women - Betts, Julian R. [Verfasser] (My University, 2001)
"The article measures the impact of high school resources on women's educational attainment and earnings. Not link emerges between education and school resources - as measured by the pupil- teacher ratio, spending per pupil, teachers' starting salaries, or books per student. For white women, no significant connection between school resources and wages is found. But school inputs are in several cases significantly and positively related to black women's wages. Wage elasticities with respect to school inputs are uniformly larger for black women. Finally, the impact of school resources on earnings remains constant or in some cases weakens as workers grow older." (author's abstract, IAB-Doku) ((en))
Keywords: G 2.3.1 Arbeitsteilung & -organisation; G 1.3.3.4 Wiedereingliederung; G 1.2.2.1 Lohn- & Tarifsysteme; I 2.3.2 Nordamerika; Schule; Auswirkung; Berufliche Integration; Lohnhöhe; Frauen; Quantitative Angaben; USA